Media issues and impact: From positivism to phenomenology, audience attitudes and concerns - social media and shopping malls as 'ready-to-hand' - Wilson, Tony * (2012)
Consumers engage with branded space, time, and products therein, responding immersively to digital marketing or downtown malls. What media (in)formed or materially shaped mode of audience address is appropriate to these perceptive participants? In turn, are their responses therein reasonably rendered merely as affirming or negative attitudes to media promoted product or people, subsequently to be quantified as conjoined with variables by which they are argued inductively to be (normally) caused/ We argue rather for replacing the reductionist concept of attitude. Authoring audiences construct mall and media narratives in a 'ready-to-hand'(Heidegger) or tacit practice of assembling stories. Discussion with media users unpacks that process by reflecting upon people's core activity of intending or projecting meaning from their horizon of understanding narrative as generic. Explicitly or implicitly, audiences anticipate realizing intelligibility on screen. Drawing upon responses to YouTube marketing narratives, our paper presents 'present-at-hand' (Heidegger) projections in focus groups. In a hermeneutic circle of understanding stories, participants can constitute a coherent synthesis of projection and subsequent event on screen. We discuss the discourse in which they reflect upon successfully syntheses. Marketing narratives are considered to be prescriptive: we examine audience alignment or alienation from evaluation.